Histopathologic Features of Mycobacterium ulcerans Infection - Jeannette Guarner; Jeanine Bartlett; Ellen A. Spotts Whitney; Pratima L. Raghunathan; Ymkje Stienstra; Kwame Asamoa; Samuel Etuaful; Erasmus Klutse; Eric Quarshie; Tjip S. van der Werf; Winette T.A. van der Graaf; C. Harold King; et al. (Emerging Infectious Diseases, 2003)
Because of the emergence of Buruli ulcer disease, the World Health Organization launched a Global Buruli Ulcer Initiative in 1998. This indolent skin infection is caused by Mycobacterium ulcerans. During a study of risk factors for the disease in Ghana, adequate excisional skin-biopsy specimens were obtained from 124 clinically suspicious lesions. Buruli ulcer disease was diagnosed in 78 lesions since acid-fast bacilli (AFB) were found by histopathologic examination. Lesions with other diagnoses included filariasis (3 cases), zygomycosis (2 cases), ulcerative squamous cell carcinomas (2 cases), keratin cyst (1 case), and lymph node (1 case). Thirty-seven specimens that did not show AFB were considered suspected Buruli ulcer disease cases. Necrosis of subcutaneous tissues and dermal collagen were found more frequently in AFB-positive specimens compared with specimens from suspected case-patients (p<0.001). Defining histologic criteria for a diagnosis of Buruli ulcer disease is of clinical and public health importance since it would allow earlier treatment, leading to less deforming sequelae.